ChemInform Abstract: Studies on the Aza‐Claisen Rearrangement of 7‐ to 9‐Membered Vinylazacycles. Issue 35 (August 2016) - Jung, Jong‐Wha; Suh, Young‐Ger; Kim, Seok‐Ho; Lee, Won‐Il; Kim, Seon‐Mi; Jung, Jae‐Kyung; Jang, Jaebong; Sim, Jaehoon
Abstract: The amide enolate‐induced aza‐Claisen rearrangement of the vinylazacycles furnishes 11‐ to 13‐membered macrolactams with an internal (E)‐olefinic bond, not accessible by conventional methods.